1992
DOI: 10.1103/physrevb.45.7127
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Raman scattering in layered cuprate materials

Abstract: The line shape of Raman scattering in a two-dimensional Heisenberg antiferromagnet at zero temperature is studied within spin-wave theory, by using the Dyson-Maleev transformation.Besides the wellknown dominant contribution coming from two-magnon scattering, a systematic analysis of the contribution coming from the production of four magnons is carried out. It is found that the four-magnon contribution is very small compared with the two-magnon intensity. However, it occurs at such large energies that the rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
178
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(203 citation statements)
references
References 33 publications
24
178
1
Order By: Relevance
“…Eqs. (5) and (6) yield a two-magnon peak at ∆ω = 2.8J (for S = 1/2), but R(ω) clearly contains no dependence on the incident photon frequency ω i [11,15]. As mentioned earlier, the LF theory is only valid for small ω i .…”
Section: The Formalismmentioning
confidence: 93%
See 2 more Smart Citations
“…Eqs. (5) and (6) yield a two-magnon peak at ∆ω = 2.8J (for S = 1/2), but R(ω) clearly contains no dependence on the incident photon frequency ω i [11,15]. As mentioned earlier, the LF theory is only valid for small ω i .…”
Section: The Formalismmentioning
confidence: 93%
“…It has already been emphasized several times in the literature that the dominant contribution to the magnon-magnon scattering comes from the region near the magnetic Brillouin zone boundary where the antiferromagnetic magnons behave almost as free particles [11,28]. In this situation, the only relevant interaction term has two creation and two annihilation magnon operators:…”
Section: The Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman and neutron diffraction experiments evaluate this coupling to be around J N N =130 meV(128±6 meV [1,2],134±5 meV [3,4,5], respectively). Nevertheless, the corresponding simple Heisenberg Hamiltonian does not reproduce entirely the features of the Raman spectrum [6,7,8,9,10,11] and additional effects such as second-neighbor magnetic coupling J N N N and four-spin cyclic exchange have been invoked [12,13,14,15]. While an upper bond for J N N N (|J N N N | ≤9 meV) has been given from Raman experiments [5], the amplitude of the four-spin operator in this kind of compounds is a matter of discussion.…”
Section: Introductionmentioning
confidence: 99%
“…We review possible sources of the high-energy spectral weight which were suggested in the past, e.g. quantum fluctuations 26,41,42,43,44,45 , the role of spin-phonon interaction 4, 46,47,48,49,50,51 and the triple resonance 5, 52,53,54 . In case of the cuprate planes no final conclusion concerning the origin of the high-energy weight can be drawn, but in the case of the cuprate ladders the spin-phonon coupling and the triple resonance can be ruled out.…”
Section: Introductionmentioning
confidence: 99%